2015
DOI: 10.1155/2015/713043
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Size of Combinatorial Optimization Problems Using the Operator Vaccine by Fuzzy Selector with Adaptive Heuristics

Abstract: Nowadays, solving optimally combinatorial problems is an open problem. Determining the best arrangement of elements proves being a very complex task that becomes critical when the problem size increases. Researchers have proposed various algorithms for solving Combinatorial Optimization Problems (COPs) that take into account the scalability; however, issues are still presented with larger COPs concerning hardware limitations such as memory and CPU speed. It has been shown that the Reduce-OptimizeExpand (ROE) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Size reduction is naturally the most crucial procedure in the PSR process since better decisions in this step will produce solutions of better quality in the subsequent stages (Montiel et al, 2013;Montiel & Delgadillo, 2015;Delgadillo et al, 2016). Strategies to make these decisions are highly dependent on the structure and features of the problem, so they vary significantly among distinct classes of COPs.…”
Section: Problem Size Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size reduction is naturally the most crucial procedure in the PSR process since better decisions in this step will produce solutions of better quality in the subsequent stages (Montiel et al, 2013;Montiel & Delgadillo, 2015;Delgadillo et al, 2016). Strategies to make these decisions are highly dependent on the structure and features of the problem, so they vary significantly among distinct classes of COPs.…”
Section: Problem Size Reductionmentioning
confidence: 99%
“…Studies found in the literature in which PSR has been successfully applied to routing problems include those by Gavish & Srikanth (1986), Min (1991), Barnhart et al (2002), Fischer & Merz (2007), Ramos & Oliveira (2011), Lin (2011), Montiel et al (2013), Montiel & Delgadillo (2015) and Delgadillo et al (2016).…”
Section: Problem Size Reductionmentioning
confidence: 99%
“…In this work, we are encouraged finding the optimal solution for 3D pose estimation problem when the target can present abrupt pose changes in the scene, i.e., when the search space of location, orientation, and scaling parameters of the target is very big. This challenge needs to be treated as a combinatorial optimization problem that can become numerically intractable as the number of feasible poses of the target increases [16,17]. From the point of view of computational complexity, this problem is classified as an NPhard problem [18], since it will require an algorithm with the ability to solve problems in nondeterministic polynomial (NP) time, but the solution can be verified in polynomial time.…”
Section: Introductionmentioning
confidence: 99%